Peripartum Cardiomyopathy - Rodríguez-González, Miguel A.; Medina-Ruíz, Arturo (Puerto Rico Health Sciences Journal, 2006)
Peripartum cardiomyopathy (PPCM) is a condition that affects women during the reproductive years in the late pregnancy period and/or early postpartum period. Although it is associated with several risk factors and various hypotheses exist of its etiology the cause of this disorder is still unknown. Standard therapy for PPCM is the same as for heart failure. Studies examining new therapeutic approaches are adding to the armamentarium available to physicians treating patients with PPCM. Despite all the current knowledge the mortality rates associated with PPCM remain relatively high. This article is a review of the current knowledge of etiology, diagnosis, treatment and prognosis of PPCM and attempts to present areas of need of further research.